Assessment of the interphase drag coefficients considering the effect of granular temperature or solid concentration fluctuation via comparison of DNS, DPM, TFM and experimental data. (21st September 2020) - Bian, Wei; Chen, Xizhong; Wang, Junwu
Highlights: Detailed comparison between DNS, DPM and TFM was performed. Including state variable fluctuation in drag coefficient has a minor effect. DPM and TFM underestimate the anisotropy of local granular temperature. DPM and TFM cannot go through the phase space of interphase momentum exchange rate. Abstract: Highly-resolved simulations using two-fluid model (TFM) and discrete particle method (DPM) have indicated that the true interphase drag force of gas-solid system was underestimated by currently available drag correlations. Meanwhile, recent direct numerical simulations (DNS) have concluded that there is a need to consider the effect of the fluctuation of state variables on the interphase drag force, which results in an increase of the effective interphase drag force. Therefore, it is interesting to see how much improvement can be achieved when those drag coefficients are used. To this end, extensive TFM and DPM simulations were performed to assess the drag coefficients that consider the effect of granular temperature or solid concentration fluctuation, using the experimental and DNS data of Tang et al. (2016a), Luo et al. (2016) and Müller et al. (2008) as the benchmarks. It was found that (i) all currently available drag correlations that have included the fluctuation of state variables can only have a minor impact on simulation results as compared to the difference caused by using different basic drag correlations; they are insufficient to fill in the gap between DPM/TFM and DNS results; (ii) DPM simulations offer a much better agreement with DNS results, especially when compared to the DNS results of Luo et al. (2016); (iii) the local and global granular temperatures of DNS, DPM and TFM are in a fair agreement, but the anisotropy found in DNS is underestimated by DPM and TFM; and (iv) TFM cannot go through all of the phase space of interphase momentum exchange rate found in DNS, due to the averaged treatment in those methods. Present study highlights the need of a better model or correlation for the effective interphase drag coefficient.